Synthesis, biological evaluation and molecular docking studies of 2-piperazin-1-yl-quinazolines as platelet aggregation inhibitors and ligands of integrin αIIbβ3 - Krysko, Andrei A; Kornylov, Alexander Yu; Polishchuk, Pavel G; Samoylenko, Georgiy V; Krysko, Olga L; Kabanova, Tatyana A; Kravtsov, Victor Ch; Kabanov, Vladimir M; Wicher, Barbara; Andronati, Sergei A (Bioorganic & medicinal chemistry letters, 2016)
A series of 2-piperazin-1-yl-quinazolines were synthesized and evaluated for their antiaggregative activity. The synthesized small molecule compounds have potently inhibited platelet aggregation in vitro and blocked FITC-Fg binding to αIIbβ3 integrin in a suspension of washed human platelets. The key αIIbβ3 protein-ligand interactions were determined in docking experiments and some correlations have been observed between values of the affinity and docking scores.
Keywords: piperaziny; simulace molekulového dockingu; Platelet Aggregation; trombocyty; Quinazolines; lidé; Platelet Aggregation Inhibitors; Platelet Glycoprotein GPIIb-IIIa Complex; agregace trombocytů; α(IIb)β(3); Blood Platelets; Ligands; Platelet aggregation; Piperazines; Fibrinogen receptor antagonists; chinazoliny; 2-Piperazin-1-yl-quinazoline; trombocytový glykoproteinový komplex IIb-IIIa; inhibitory agregace trombocytů; Molecular Docking Simulation; ligandy; Humans